Systemic lupus erythematosus arthropathy: the sonographic perspective. (April 2018) - Di Matteo, A; De Angelis, R; Cipolletta, E; Filippucci, E; Grassi, W
Background: Despite being promising, the use of ultrasound (US) in the assessment of musculoskeletal manifestations of systemic lupus erythematosus (SLE) is still limited. Literature on this topic is scarce and the spectrum and clinical relevance of US abnormalities has not yet been outlined. With this paper, we aim to explore the panel of joint and tendon US findings in a group of SLE patients. Methods: Twenty-five consecutive SLE patients, with current or medical history of musculoskeletal symptoms, were studied. All patients underwent routine clinical examination and US evaluation. The US examination targeted sites clinically involved in the physical examination and/or indicated as painful in the patient's medical history. Results: One or more US changes were found in all the patients. US abnormalities were detected in 85 out of the 243 scanned joints (35%), in 70 out of the 215 scanned tendons (32.6%) and in 10 out of the 41 scanned entheses (24.4%). Synovial effusion, synovial hypertrophy, "mixed" synovitis (coexistence of synovial effusion and synovial hypertrophy), joint dislocation, bone erosion, and cartilage damage were found in 9.5%, 11.5%, 14%, 3.7%, 2.1%, and 4.5% of the scanned joints, respectively. Tenosynovitis, tendon dislocation, tendon tear, tendon thinning, and tendinitis/peritendinitis were detected in 17.7%, 8.4%, 0.9%, 4.2%, and 4.7% of the scanned tendons, respectively. Power Doppler signal, hypoechogenicity, thickening, enthesophytes, calcifications, and bone erosions were detected at the entheseal level in 12.2%, 9.8%, 12.2%, 7.3%, 7.3%, and in 0% of the scanned entheses, respectively. Conclusions: This study revealed an unexpectedly wide heterogeneity of US pathologic findings in the joints and tendons of patients with SLE. A broad spectrum of US changes also involving anatomic structures not considered in previous investigations, including entheses and tendons with no synovial sheath, was detected. These preliminary results suggest that US is able to identify several US "patterns" whose clinical, prognostic, and pathogenetic significance is still to be defined.